Rare diseases epidemiology : update and overview - Posada de la Paz, Manuel; Taruscio, Domenica; Groft, Stephen C. (Springer, 2017)
This second edition of the book about Rare Diseases Epidemiology aims to highlight the progress of rare diseases research and related activities since the first volume published. As with the previous book, this update provides a comprehensive list of issues and adds new authors who are leaders in their different areas of expertise related to rare diseases at national and international levels. Rare diseases and orphan drugs are challenges for patients and families but also for physicians, researchers, and policy-makers in both the public and private sectors. This book aims to help all of them to address topics like health care policies, societal issues and clinical and experimental research. Readers will discover methods and procedures to address a variety of questions like cases of undiagnosed rare diseases, patient registries and biobanks, health care and public health approach to rare diseases, orphan drugs and new therapies, cost-effectiveness analyses, prevention, clinical and epidemiology of individual and groups of related rare diseases, novel advances in study design and data analyses, national and international policies and social issues. Within each one of these general issues, advances, new challenges and opportunities to address significant health care issues are described across thirty-two chapters. Editors and all authors providing chapters include globally recognized experts in different areas of rare diseases, including epidemiology, public health, health economics and pharmacology, statistics, and basic, clinical and translational research. People engaged in policy formulation decisions on rare diseases as well as patient representatives relate their own point of view about social constraints they live under on a daily basis. Renowned research investigators, highly-skilled clinicians, and recognized patient leaders are included as contributing authors to this new book about rare diseases. In fact, two of the editors are the current President and President Elect of the International Conference on Rare Diseases and Orphan Drugs and the third one is a board member of this society. The book has been written for all stakeholders but mainly for those involved in the many issues related to rare diseases. They can discover new ways for dealing with important matters related to the prevention, diagnosis, natural history, treatments, and research of rare diseases and the development of orphan products.
Keywords: Rare diseases -- Epidemiology.; elektronické knihy; electronic books